TOLERANSI MASYARAKAT DI SURABAYA TERHADAP ETNIS TIONGHOA - Khoirun Nissa; Ahmad Perwira; Al Qodar Purwo Sulistyo (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
This writing discusses the tolerance of living in harmony with various ethnic groups in Surabaya in the history of social interactions that have occurred between the people of Suarabaya. Surabaya has so far lived in a multicultural manner, between residents no longer discriminatively discriminate on issues of ethnicity, religion and level of social welfare among fellow citizens, can live in harmony and side by side with one another. This condition is due, among other things, to long historical factors and a willingness to accept differences as an inevitability of social life. Surabaya values diversity and equality. According to Fikser, in this city, all kinds of ethnicities, tribes or races can be found. Starting from the Javanese, Batak, Karo, Papua, Madura, Dayak, Bugis, and so on. In addition, there are also Chinese, Arab, Indian and Korean communities. The attitude of respect for differences and diversity shown by the people of Surabaya is very compatible with the spirit of multiculturalism that has developed in the last few decades. As is known, multiculturalism is an understanding that recognizes differences in equality, both individually and in groups, within a cultural framework.